Polityka programowa Polskiego Radia w latach 1925–1929. Założenia i praktyka - Kaszuba, Elżbieta (Przegląd Nauk Historycznych, 2013)
This article focuses on the issue of policy towards the radio program outlined by Polish Radio between 1925–1929. The model of the radio adopted in Poland was that of a monopolistic public utility institution. Polish Radio was a privatestate company. It operated in a media system controlled by the government. In the twenties these control functions of the state were purely formal. In such circumstances the private share-holder became a policy maker in the area of radio program and was responsible for carrying out a mission for the benefit of the state and society. At the same time the private licensee preferred the commercial model of radio. These factors clearly determined the pace of professionalisation of broadcasting. This phase of Polish Radio activity was characterized by the lack of a creative and conceptual approach to the radio program.